Automatic Plant Irrigation System - Shiva Kumar S., Ajay J. V., Kusha B., Dr. Venkateshappa (International Journal of Modern Agriculture, 2021)
In activities associated with gardening and farming the critical activity is watering which is also labor intensive.The different weather conditions include dryness , wetness, hotness, cloudiness in the atmosphere. In all these weather conditions it is imperative that the quantity of water that reaches the plants is controlled. The watering systems used presently are effective in providing the required amount of water to the plants. This manual watering process must consider two important issues: quantity of water provided to plants and the time during the day at which water is provided. Our goal in the project is replacement of manual activities. This has the potential to make the gardener's work more easier. This goal is achieved by creating a watering system for plants which works automatically.When the above system is installed in agriculturalfield or thegardentheplants will get sufficient water for their growth and also water isconserved. The system is a combination of dripemitters and sprinklers. The implementation of the system makes use ofnozzles,pipes andsprinkler systems. The proposed system uses the micro-controller ATmega328. This isprogrammed for sensing level ofmoisture in plants at the required time. A moisture threshold is predefined depending on the need of the particular plant. When the quantity of moisture becomes less than the threshold level the needed amount of water is provided to the plant until the moisture level reaches the predefined threshold value. All plants require water two times a day, specifically during morning and also during evening. Programming the microcontroller for the above requirement ensures that plants get the required water. The system reports the present state to the user and the user is sent remainders to ensure that water is added to the tank. These notifications are implemented using mobile apps. The prototype system developed makes gardening and farming activities an enjoyable experience and there are no issues to worry like forgetfulness.